Impact of Student Leaders’ Participation in School Peer Counseling Programs on Learners’ Discipline in Public and Private Secondary Schools in Machakos Sub-County, Kenya - Luti-Mallei, Rose Mueni; Gakunga, Daniel Komo; Nungu, Musembi (International Journal of Learning and Development, 2024)
This paper focuses on student leaders’ participation in school peer counseling programs as a valuable strategy of student leaders’ integration in school governance. Intensive involvement of student leaders in school peer counseling programs is a worthwhile link between the students’ body, teachers and the school administration. It is an opportunity for the student leaders to interact and share with the students’ body as they air their views and concerns on academic and discipline issues in the school. Utilization of the information gathered from peer counseling forums by the school administrators in decision making translates to impressive learners’ discipline and academic performance. The study was carried out in Machakos sub-county, Machakos County, Kenya to investigate the impact of student leaders’ participation in school peer counseling programs on learners’ discipline in public and private secondary schools. The study was guided by two objectives; to establish the status of student leaders’ participation in school peer counseling programs and establish the impact on learners’ discipline. The study embraced a descriptive survey design. Simple random sampling and purposive sampling were employed to get the Sample size. Data were collected using questionnaires for the students and teachers and interview schedules for the deputy principals, principals, Board of Management (BoM) chairpersons, and directors of private schools. Further, relevant documents were scrutinized for triangulation of the information provided by the respondents. The data collected was processed using Statistical Package for Social Sciences version 21. The statistics were tabulated and subjected to regression analysis using ANOVA and coefficient models. The study established student leaders’ participation in school peer counseling programs as a golden chance for student leaders to interact with fellow learners’ as they express views and suggestions on school routines, rules, and regulations. Action on gathered information created a peaceful school environment suitable for mentoring learners. The result was improved learners’ discipline. In contrast, student leaders who did not actively and openly interact with other learners missed an opportunity to gather information on learners’ views and hence did not identify real issues affecting learners for the school administration action. The study concluded that participation of student leaders in school peer counseling was significantly higher at (p) 0.003 than student leaders not participating in school peer counseling programs (p) 0.047. Hence the null hypothesis was rejected. The study recommended that school principals and other school administrators should organize frequent school peer counseling programs and encourage student leaders and other learners to air their views.